Chapter La nuova frontiera del viaggio: l'esplorazione del cosmo - Romoli, Marco (Studi e saggi, 2021)
The human drive for knowledge, together with the technology development, often accelerated by warfare, has opened new frontiers to exploration. Once the exploration of the Earth globe came to an end with the conquest of the geographical poles, of the high mountains, and the ocean deeps, mankind developed new attention to Space and the exploration of the Universe, not only by means of ground based telescopes, but with rockets, unmanned and manned satellites and spacecrafts. In the mid of XX century, the drivers are similar to those that pushed the Nations of XV century to discover the world: geopolitics strategies, hunger for resources and knowledge, conquer and adventure. We are just at the beginning. This is a brief overview of the Space Age history and of the present and future development.